فراق گورکھ پوری کی اقبال فہمی : تحقیدی مطالعہ: Firaq Gorakhpuri’s Understanding of Iqbal: A Research Study - اقبال ڈاکٹر محمد عامر (Tashkeel e Jadeed, 2024)
Firaq Gorakhpuri gained fame in the field of romantic poetry. His imagination was strong, mood was soft, and tone was beautiful. In his words, similes, metaphors and interpretations are often miraculous. Firaq's poetry is popular in life itself. The effects of his poetry gradually appear on the mood of the reader. Firaq could not be distinguished in the field of research and criticism. His criticism of Iqbal's thought is not only unbalanced but also has an element of contempt. Iqbal's appreciation of India and its inhabitants, no other poet could express such pain and such sincerity. His opinion regarding Iqbal never seemed balanced. Iqbal helped Josh Malihabadi a lot, but Josh acted with malice against Iqbal in one of his interviews. Josh did not realize the complexities of his own themes and ideas. Josh's poems are deeply thought-provoking. Firaq also forbade Josh from opposing Iqbal by writing a long letter. In terms of criticism, Firaq's objections proved frivolous and lost their impact.